Terapi Opioid pada Kasus COVID-19 - Jufan, Akhmad Yun; Kurniawaty, Juni; Dewi, Baiq Dessy Resmana (Jurnal Komplikasi Anestesi, 2021)
One-third of COVID-19 patients experience a variety of neurological symptoms involving the central and peripheral nervous systems. These symptoms include headache, dizziness, loss of consciousness, impaired smell, neuralgia, and skeletal muscle damage. Myalgia is the most common symptom in cases of COVID-19. Therefore, adequate pain management isneeded, one of the choices is using opioids. Opioid receptor agonists are a group of drugs that stimulate opioid receptors and produce their effects by mimicking endogenous opioid peptides known as endorphins.